A phase II study of laser interstitial thermal therapy combined with doxorubicin in patients with recurrent glioblastoma. Issue 1 (15th November 2021) - Butt, Omar H; Zhou, Alice Y; Huang, Jiayi; Leidig, William A; Silberstein, Alice E; Chheda, Milan G; Johanns, Tanner M; Ansstas, George; Liu, Jingxia; Talcott, Grayson; Nakiwala, Ruth; Shimony, Joshua S; et al.
Abstract: Background: The blood-brain barrier (BBB) is a major limiting factor for drug delivery in brain tumors. Laser interstitial thermal therapy (LITT) disrupts the peritumoral BBB. In this study, we examine survival in patients with recurrent glioblastoma (GBM) treated with LITT followed by low-dose doxorubicin, a potent anti-neoplastic drug with poor BBB permeability. Methods: Forty-one patients with recurrent GBM were enrolled; thirty patients were evaluable. Participants underwent LITT followed by 6 weekly doxorubicin treatments starting within one week (Early Arm) or at 6–8 weeks (Late Arm) after LITT. The overall survival (OS), local progression-free survival (PFS), and any PFS were compared to historical controls treated with bevacizumab salvage therapy ( n = 50) or LITT with standard BBB-permeable salvage therapy ( n = 28). Cox proportional-hazards models examined the contribution of age, gender, MGMT promoter status, and IDH -mutation status on any PFS and OS. Adverse events were also cataloged. Results: The Late Arm and all patients (Early Arm + Late Arm) demonstrated significant improvement in OS compared to historical controls treated with bevacizumab ( p < 0.001) and LITT with standard salvage therapy ( p < 0.05). No significant difference in any PFS was observed between either arm and historical controls. Low-dose doxorubicin was well tolerated with comparable adverse event rates between the arms. Conclusions: Low-dose doxorubicin given after LITT is well tolerated and correlated with higher OS compared to historical controls treated with bevacizumab or LITT with standard salvage chemotherapy. A larger study is needed to further characterize survival and progression patterns.